1990
DOI: 10.1177/0093854890017002001
|View full text |Cite
|
Sign up to set email alerts
|

The Competence Assessment for Standing Trial for Defendants with Mental Retardation (Cast-MR)

Abstract: The purpose of this study was to develop and validate an instrument for the assessment of competence to stand trial in criminal defendants with mental retardation. Three experiments were conducted on the instrument developed, Competence Assessment for Standing Trial for Defendants with Mental Retardation (CAST-MR). Experiment 1 consisted of three pilot testings with mentally retarded group home residents, Experiment 2 an expert appraisal process and readability analysis, and Experiment 3 a field testing with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…N = 75. a = never; b = infrequently; c = occasionally; d = about 50% of the time; e = frequently; f = almost always; g = always; TM = total mentions; WS = weighted scores (sum of n × numerical weight of ratings: a = 0, b = 1, c = 2, d = 3, e = 4, f = 5, g = 6). (Wechsler, 1992) 96 13 (Pascal & Suttell, 1951) 43 9 17 3 2 0 3 34 78 Luria-Nebraska Neuropsychological Battery (Luria, 1965) Everington & Luckasson, 1992) were the next most commonly used. The results for this category also included the family of instruments by Grisso (1998) to evaluate competency to waive Miranda Rights and an instrument by Rogers (1984) to assess criminal responsibility (i.e., The Rogers' Criminal Responsibility Assessment scales).…”
Section: Survey Instrument and Proceduresmentioning
confidence: 99%
“…N = 75. a = never; b = infrequently; c = occasionally; d = about 50% of the time; e = frequently; f = almost always; g = always; TM = total mentions; WS = weighted scores (sum of n × numerical weight of ratings: a = 0, b = 1, c = 2, d = 3, e = 4, f = 5, g = 6). (Wechsler, 1992) 96 13 (Pascal & Suttell, 1951) 43 9 17 3 2 0 3 34 78 Luria-Nebraska Neuropsychological Battery (Luria, 1965) Everington & Luckasson, 1992) were the next most commonly used. The results for this category also included the family of instruments by Grisso (1998) to evaluate competency to waive Miranda Rights and an instrument by Rogers (1984) to assess criminal responsibility (i.e., The Rogers' Criminal Responsibility Assessment scales).…”
Section: Survey Instrument and Proceduresmentioning
confidence: 99%
“…The development of several research-validated competence assessment scales has provided reliable instruments that can easily be used on an outpatient basis, and do not require extensive legal knowledge to administer or score (Grisso, 1986;Schreiber, Roesch, & Golding, 1987). In particular, the MacArthur Competence Assessment Tool-Criminal Adjudication (Otto et al, 1998) for competence in general populations, and the Competence Assessment for Standing Trial in Mentally Retarded Defendants (Everington & Luckasson, 1992), provide scores that can be compared with study samples of defendants independently found competent and incompetent to stand trial.…”
Section: Current Advantages and Disadvantages Of Inpatient Evaluationmentioning
confidence: 99%
“…The Competence Assessment to Stand TrialMental Retardation (CAST-MR: Everington & Luckasson, 1992) assesses competence in three areas related to the court system -basic legal concepts, skills to assist defence and understanding of case events. The CAST-MR was used by 45% of psychologists surveyed about practices used when evaluating juvenile competence to stand trial (Ryba, Cooper & Zapf, 2003).…”
Section: Assessment Issuesmentioning
confidence: 99%